2006
DOI: 10.2174/157489006775244263
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Endothelin System in Hypertension - Recent Patents and Discoveries

Abstract: The discovery of endothelin two decades ago has now evolved into an intricate vascular endothelin (ET) system. Several ET isoforms, receptors, signaling pathways, agonists, antagonists, and clinical applications have been identified and documented in first-rate patents. The role of ET as one of the most potent endothelium-derived vasoconstricting factors is now complemented by a newly discovered role in vascular relaxation. ET synthesis is initiated by the transcription of ET genes in endothelial cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 82 publications
1
105
0
5
Order By: Relevance
“…ETa is a kind of endothelin receptor. Binding endothelins to ETa will result in vasoconstriction and an increase in blood pressure (Hynynen and Khalil 2006). Previous studies also reported that ETa antagonists could block the endothelin-induced effects and prevent cardiovascular diseases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ETa is a kind of endothelin receptor. Binding endothelins to ETa will result in vasoconstriction and an increase in blood pressure (Hynynen and Khalil 2006). Previous studies also reported that ETa antagonists could block the endothelin-induced effects and prevent cardiovascular diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelins can induce vasoconstriction and play a key role in the regulation of vascular tone (Kedzierski and Yanagisawa 2001). Previous studies suggested that endothelins were involved significantly in the regulation of hypertension (Hynynen and Khalil 2006). Upregulation of the endothelin system occurred in human hypertension and experimental animal models of severe hypertension (Schiffrin 2001).…”
Section: Discussionmentioning
confidence: 99%
“…16 An upregulation of the ET1 system has been linked to numerous pathologies, including salt-sensitive hypertension. 20,21,32,33 Because of these functions the endothelin system might in large part contribute to the hypertrophy and the endothelial dysfunction observed in DOCA-salt hypertension. In an attempt to test this we (i) treated DOCA-salt hypertensive rats for 3weeks with the NEP/ECE inhibitor SOL1 and (ii) studied the endothelium-dependent structural effects of imposed changes in blood flow in DOCA salt hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Travma veya enflamasyon sırasında salıverilen vazokonstriktör mediyatörler ET salıverilmesini uyarmaktadır. Endotelin salıverilmesini indükleyen ve önleyen mediyatörler Tablo 1'de belirtilmiş-tir (52)(53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Endotelin-1'in Ekspresyonu Ve Etkinliğinin Düzenlenmesiunclassified